Design of the board of environmental series and time to improve skills to speak BIPA students - Randi Ramliyana (Universitas Indraprasta PGRI, 2018)
learning difficulties faced by Indonesian Language students for Foreign Speakers (BIPA)in speaking classes at beginner level are still felt. they still experience confusion, especially inmaterial numbers and time. they not only need ease in remembering material, but also excitement inremembering it. Therefore, the researcher designed a teaching media specifically designed toimprove the speaking skills of beginner-level BIPA students in material numbers and time. Thisteaching media is in the form of an awesome text. This board is designed to improve students'speaking skills in a different way than usual. like the visual teacher alliance, visual media canincrease 400% of student learning in the classroom. based on this, the researchers made a powerfulcrankshaft in the form of an image. The purpose of this study was to describe the design of thecrunch board teaching media with a series of numbers and times that can improve students' speakingskills in different ways.